Agriculture, trade reform and poverty reduction : implications for Sub-Saharan Africa - Anderson, Kym (UN New YorkUS, 2004)
Explores the poverty implications of the current post-Doha multilateral trade reform agenda of the WTO for developing countries, so those benefits can be weighed against perceived adjustment costs. Addresses the effects of trade reform on poverty at three levels: first on developing countries as a group; then on different types of developing countries; and finally on different types of households within developing countries. Addresses such questions as whether food-importing countries would suffer from higher food prices in international markets, and what impact reform could have on food security and poverty alleviation.